KAJIAN HAKIKAT PENDIDIKAN ISLAM MELALUI PENDEKATAN ONTOLOGIS, EPISTEMOLOGIS, DAN AKSIOLOGIS - Junaidi, Mohammad Mahbub; Fitriani, Rena Dwi; Haris, Abd. (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This paper explores the essence of Islamic education through the philosophical dimensions of ontology, epistemology, and axiology. ontologically, the human being is viewed as a spiritual-rational entity endowed with innate nature (fitrah), soul (ruḥ), intellect (ʿaql), and heart (qalb), all of which require holistic development through education. from the epistemological perspective, Islamic education recognizes divine revelation as the primary source of knowledge, complemented by reason, intuition, and experience, and is operationalized through bayani, burhani, and ʿirfani methods. axiologically, Islamic education aims to form the ideal human (insan kamil) by internalizing values such as tawḥīd, ethics (akhlāq), justice, compassion, and public welfare. the integration of these three philosophical foundations positions Islamic education as a transformative system that advances not only scientific knowledge but also moral character and civilizational integrity. this study concludes by recommending a revitalized, integrative, and value-based Islamic educational model capable of addressing contemporary global challenges.